(3QSGdI aj GdenqYeis - (3CMeO Hf SdjeGfs ((3LYaQ GdNQSGf s)
(3ChdgG (B:s
(3GeG HYO(B: (3adeG cGf ddCOH WQGFb WQGFa, hCSGdjH XQGFa GSJNQL WGFaI ef GdYLe afkG Sehg GdYei, hGHJcQhG ajg GdNjGdGJ GdObjbI dGSJNQGL GdCSeGA s
(3BNQgG (B:s
(3Edi ef gh ddYjf bQI hddbdH aQMkG heSQI, Edi GdeTGQ Gdjg ai GdaVGFd hGdCOH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdeDda ef JdGejP TgGH GdOjf Hf CMeO Hf ehSi Gdecis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B34 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjI Gddg GdMcje GdYGeg (B- (3GdfLa (B(287) s
Keywords: (3GdCOHs